Pengaruh PAD, DAU Dan DAK Terhadap Belanja Daerah Provinsi Lampung - Ega Santika; Amelia Anwar; Astrid Aprica Isabella (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of Regional Original Revenue, General Allocation Funds, and Special Allocation Funds affecting Regional Expenditures in the Provinces of Lampung. This type of research is quantitative research. The Saturated Sampling Method was used in selecting a sample of 15 districts/cities in Lampung 2018-2022 periode, the technique of selecting samples in this study uses purposive sampling method with the amount of data that is processed as many as 75. The data analysis technique uses multiple linear regression analysis with SPSS version 25. Based on the results of the study it is known that Local Own Revenue, Special Allocation Funds have and General Allocation Funds have a positive effect Partially on Regional Expenditures. Simultaneous tests show the results that the variables Regional Original Income, General Allocation Funds, and Special Allocation Funds jointly affect Regional Expenditures.